PERUBAHAN PERILAKU SOSIAL KEAGMAAN PADA JAMAAH TAREKAT NAQSABANDIYAH DI PASAMAN BARAT : PERSPEKTIF TINDAKAN SOSIAL MAX WEBER - Dina Lorenza; Abdul Gaffar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The change in religious social behavior is one of the most intriguing social phenomena to study within the context of a religious community. In Pasaman Barat, the zikr practice performed by the congregation of the Naqshbandiyah Order at Surau Baiturrahman Lubuak Landua has a significant influence on shaping character and religious social behavior. This study aims to examine how zikr practices within the Naqshbandiyah Order contribute to the transformation of the congregation’s religious social behavior and to analyze it through the perspective of Max Weber’s theory of social action. This research employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. The informants consisted of the mursyid, khalifah, and members of the Naqshbandiyah congregation. Data were analyzed through stages of data reduction, presentation, and conclusion drawing, with data validity ensured through source and method triangulation. The findings reveal that collective zikr activities play a vital role in fostering discipline, patience, sincerity, and social awareness among the congregation. From Max Weber’s perspective, the congregants’ behavior reflects four types of social action: value-rational, instrumental-rational, traditional, and affective actions. Among these, value-rational action is the most dominant, as zikr is performed with spiritual awareness as an expression of devotion to Allah SWT. Thus, the Naqshbandiyah Order plays an essential role in shaping religious, harmonious, and socially conscious behavior within the Lubuak Landua community.